Imbalances in the African Peace and Security Architecture: The current approach to capacity-building needs to be challenged - Judith Vorrath (Stiftung Wissenschaft und Politik (SWP), 2012)
Given the current crisis in Mali and the renewed rebellion in Eastern Congo, the debate over "finding African solutions to African problems" has emerged with new vehemence. Ten years after the creation of the African Union (AU), the establishment of the African Peace and Security Architecture (APSA) on the continent has progressed. But its out-comes have not met the ambitions of both African and external actors. The most com-monly cited reason for this is a lack of capacity. However, the AU's experiences have revealed that more fundamental imbalances characterize the APSA, calling for a tar-geted response from international donors
Keywords: 320